The impact of reaching the anaerobic threshold on some kinematic variables related to the accuracy of shooting the penalty kick among footballers - Ibtehal Mohammad Alkhawaldeh (Sport TK, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.